2018
DOI: 10.7861/futurehosp.5-1-58
|View full text |Cite
|
Sign up to set email alerts
|

Older people with hip fracture transferred to intermediate care: outcomes in an integrated health and social care model

Abstract: Following surgery for hip fracture almost a quarter of patients do not return directly to their usual residence, using the resources within intermediate care and enablement. This was a retrospective cohort study involving 156 Salford residents admitted with hip fracture in 2015. Linked health data were collected on those discharged to intermediate care vs home in terms of readmissions, mortality, lengths of stay, delayed transfers of care, diagnoses of delirium and pre-existing forms of dementia. The median du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Since the goal of TCP is to promote discharge home and avoid RAC admissions, these differences between countries suggest that further evaluation of TCP is required to understand what programs are most effective. Approximately 60% of the older adults who were discharged to RAC had cognitive impairment which accords with other studies that found cognitive impairment significantly reduced the likelihood of older adults returning home ( 3 , 6 , 24 ).…”
Section: Discussionsupporting
confidence: 84%
“…Since the goal of TCP is to promote discharge home and avoid RAC admissions, these differences between countries suggest that further evaluation of TCP is required to understand what programs are most effective. Approximately 60% of the older adults who were discharged to RAC had cognitive impairment which accords with other studies that found cognitive impairment significantly reduced the likelihood of older adults returning home ( 3 , 6 , 24 ).…”
Section: Discussionsupporting
confidence: 84%